Aplikasi Surat Menyurat Berbasis Android - Alsepianingsih, Feti; Esabella, Shinta (Management of Information System Journal, 2023)
Village Office is a place where used by the relevant village government to carry out administrative activities. Administrative activities that are processed include making certificates of incapacity, identity cards, family card management. Not only that, the village government also processed the domicile change letter The Village Office is one of the community service offices located in Berang Rea Village, Moyo Hulu District, Sumbawa Regency, West Nusa Tenggara. This research aims to create an Android-Based Correspondence Application at the Berang Rea Village Office, Moyo Hulu District, which aims to produce a Correspondence Application that can make it easier for people to carry out correspondence services independently and have a more attractive and easily accessible appearance via Android smartphones. The results of this study are Android-Based Correspondence Applications at the Berang Rea Village Office, Moyo Hulu District, using Extreme Programming (XP) software development methods, Unified Modelling Language (UML) modeling, and flutter darts language and using black box testing.